A Review of the Global Change Research on the Tibetan Plateau: From Field Observation to Manipulative Experiments - Yao Wei; Hua-Kun Zhou; Zhen-Hua Zhang (The Global Environmental Engineers, 2020)
Global temperature increases and precipitation changes are both expected to alter alpine ecosystem structure and processes. In this paper, we reviewed the recent climate changes observed and the global change researches on the Tibetan Plateau. Firstly, we found that the mean annual temperature and precipitation (data from 75 meteorological stations, where all daily precipitation data are available) have increased since 1971, there were 0.5˚C and 0.7˚C per decade increase in annual and winter temperature, respectively, on Tibetan Plateau, and changes in precipitation were found both less spatially and temporally consistent. Secondly, we reviewed the climate change researches on the Tibetan Plateau published between 2000 and 2019 mainly focused on plant growth and ecosystem carbon balance which including plant phenology, plant productivity, plant diversity, exchanges in ecosystem carbon and soil organic carbon. Findings and insights from these studies have been very useful to understand how the alpine ecosystem processes respond to climate change. However, the effects of temperature increase on plant growth and ecosystem carbon balance are differ depending on the study sites and warming methods and periods, and the effects of precipitation changes are sparse.